ETHICAL ANALYSIS OF THE USE OF AI IN MEDICAL DATA MANAGEMENT: PRIVACY CHALLENGES IN THE DIGITAL AGE - Farizki, Rafi (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
The use of artificial intelligence (AI) in medical data management has improved efficiency and accuracy in healthcare, but it presents significant ethical challenges, especially when it comes to patient privacy. Along with the rapid development of technology, concerns over the security and privacy violations of medical data are increasing, which can impact public trust in AI-based healthcare systems. The study aims to analyze the ethical challenges in the use of AI in medical data and identify strategies to strengthen patient safety and privacy. Using a qualitative method with a case study approach, this study involves in-depth interviews and analysis of policy documents from several health institutions. The results of the study reveal three main themes: (1) ethical challenges related to transparency and patient consent, (2) the risk of medical data leakage due to the lack of AI security standards, and (3) barriers to ethical AI implementation in the health environment, especially in developing countries. The recommendations of this study include the implementation of the latest encryption protocols, increased ethical awareness among medical personnel, and policy transparency to patients. These findings contribute to the development of medical data privacy policies in the digital era, as well as increasing public trust in AI technology in the health sector.